THE SCOPE OF SOCIALLY INNOVATIVE LEADERSHIP: HISTORICAL INSIGHTS FOR CONTEMPORARY SOCIETAL REFORM (Qualitative Research Journal for Social Studies, 2025)
This paper examines the role of incremental social innovation within a Muslim societal context, emphasizing the importance of mental models and implementation strategies as key drivers of change. Social innovation is conceptualized as a transformative phenomenon, ranging from radical to incremental shifts in how societies achieve their objectives and sustain their existence in a broader global framework. Incremental innovation, in particular, is guided by mental models that shape the innovator’s vision and supported by strategies that translate this vision into social reform. Using a case study approach and drawing evidence from historical records, this study explores the mental models and enactment tactics of incremental social innovation demonstrated under the leadership of the second Rashidun Caliph, Hazrat Umar (RA). The findings, grounded in archival sources, highlight how socially innovative leadership was applied in Islamic society to address emerging challenges. Moreover, the results corroborate contemporary global research on incremental social innovation, underscoring the enduring relevance of socially innovative leadership across cultures and historical periods.